A flexible ion chromatography column-switching system with a switching time window (STW) calibration program for the determination of myo-inositol in infant formula by pulsed amperometric detection. Issue 6 (21st March 2015) - Zhang, Shuifeng; Huang, Liying; Li, Hongyan; Chen, Xiaozhen; Wang, Fengli; Zhang, Donglei; Zhu, Yan
<x xml:space="preserve">Abstract</x> The column-switching system allows for convenient determination and calibration of STW parameters.